Prevalence of boar taint in commercial pigs from Spanish farms. (January 2016) - Borrisser-Pairó, F.; Panella-Riera, N.; Zammerini, D.; Olivares, A.; Garrido, M.D.; Martínez, B.; Gil, M.; García-Regueiro, J.A.; Oliver, M.A.
Abstract: The presence of boar taint can affect the sensory quality of pork because the "off" odours and flavours can be detected by consumers. The aim of this study was to determine the prevalence of boar taint in pig carcasses from 30 Spanish farms located in different regions of the country. Hot carcass weight and subcutaneous fat thickness means were 79.4 ± 8.19 kg and 18.4 ± 5.09 mm, respectively. Subcutaneous fat samples were classified into different levels according to androstenone and skatole concentrations in adipose tissue measured using GC–MS and HPLC. Androstenone results were: 87.4% of the carcasses below 0.50 μg/g, 7.1% from 0.50 to 1.00 μg/g (medium level), and 5.5% ≥ 1.00 μg/g (high level). Skatole results were: 88.9% of the carcasses below 0.10 μg/g, 4.5% from 0.10 to 0.20 μg/g (medium level), and 6.6% ≥ 0.20 μg/g (high level). Given these results, a future online method to classify carcasses according to boar taint is strongly recommended.